Fuel cell catalyst, method of making the same, and fuel cell comprising the same

By constructing a core-shell nanoparticle catalyst with a heterogeneous metal shell on a platinum-transition metal core, the problems of high price and limited reserves of platinum catalysts are solved, thereby improving the electrochemical reaction efficiency and redox performance of fuel cells.

CN115732707BActive Publication Date: 2026-03-17HYUNDAI MOTOR CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211052723.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-08-30
Filing Date
2022-08-30
Publication Date
2026-03-17
Estimated Expiration
2042-08-30

AI Technical Summary

Technical Problem

The high price and limited reserves of platinum, a precious metal catalyst in existing fuel cells, and the easy dissolution of transition metals under driving conditions lead to performance degradation and make it difficult to effectively improve the reaction rate.

Method used

Core-shell nanoparticle catalysts are prepared by forming a heterogeneous metal shell on a platinum-transition metal core through an electrocouple displacement reaction. The process includes a pretreatment step to remove heterogeneous metal nanocrystals from the surface, forming a uniform shell and inhibiting the dissolution of the transition metal.

Benefits of technology

It increases the active area and mass activity of the electrochemical reaction, enhances the redox reaction performance, reduces the residue of foreign metals on the catalyst surface, and improves the electrochemical reaction efficiency of the fuel cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115732707B_ABST
    Figure CN115732707B_ABST
Patent Text Reader

Abstract

This invention relates to fuel cell catalysts, their preparation methods, and fuel cells comprising the same. The fuel cell catalyst includes a conductive support and core-shell nanoparticles supported on the support. The core comprises platinum and a transition metal, and the shell comprises a dissimilar metal. The electrochemical specific activity, measured in an O2-saturated 0.1M HClO4 electrolyte solution at a scan rate of 5 mV / s and a rotation rate of 1,600 rpm within a potential range of 0.05 V to 1.05 V (vs. RHE), is 0.3 mA / cm². 2 Up to 0.6 mA / cm 2 And the mass activity is 0.05 mA / μg to 0.08 mA / μg.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Cross-reference to related applications

[0002] This application claims priority to Korean Patent Application No. 10-2021-0114866, filed on August 30, 2021, with the Korean Intellectual Property Office, the disclosure of which is incorporated herein by reference. Technical Field

[0003] This invention relates to fuel cell catalysts with increased electrochemical active surface area and high-quality activity, methods for their preparation, and fuel cells comprising the same. Background Technology

[0004] Fuel cells, which are attracting much attention as a next-generation energy source, are electrochemical devices that convert the chemical energy generated by the oxidation / reduction of fuel into electrical energy. In recent years, they have been expected to become a future power source for transportation such as electric vehicles and for home power supply.

[0005] The electrode reactions in a fuel cell consist of the oxidation of hydrogen at the negative electrode (“anode” or “oxidation electrode”) and the reduction of oxygen at the positive electrode (“cathode” or “reduction electrode”). In order for these electrochemical reactions to occur smoothly in low-temperature driven fuel cell systems (such as polymer electrolyte membrane fuel cells), the reaction rate should be effectively increased.

[0006] Therefore, the use of platinum (Pt) catalysts, a precious metal, is unavoidable in fuel cell systems. However, while platinum catalysts offer excellent energy conversion efficiency, they are extremely expensive and have limited reserves, potentially hindering the commercialization of fuel cells. Therefore, addressing the high price and limited reserves of platinum is crucial for maximizing the efficiency of fuel cell power commercialization.

[0007] Therefore, platinum-transition metal alloy catalysts have been studied recently to reduce the amount of platinum used and improve performance. However, there is a limitation that the transition metal is prone to dissolution under fuel cell driving conditions, which reduces performance. As part of the solution to this limitation, the technology of replacing the transition metal on the surface of alloy nanoparticles with a dissimilar metal suitable for fuel cell driving conditions has been studied.

[0008] However, since the substitution of transition metals on the surface occurs at the atomic level, the reaction conditions are very stringent, making effective substitution difficult. Furthermore, while galvanic substitution is advantageous because it utilizes the intrinsic standard reduction potential of the metal to gradually induce a substitution reaction between a metal with a lower standard reduction potential and a metal with a higher standard reduction potential, effectively representing atomic-level substitution is limited by the superior reducing power of dissimilar metals with high standard reduction potentials, which confine the dissimilar metals to existing as independent nanoparticles (crystals) on the catalyst surface. Summary of the Invention

[0009] This summary is provided to introduce a series of concepts in a simplified form, which will be further illustrated in the detailed description below. This summary is not intended to identify key or essential features of the claimed subject matter, nor is it intended to define the scope of the claimed subject matter.

[0010] One aspect of the present invention provides a fuel cell catalyst with high-quality activity due to the increased active surface area of ​​the electrochemical reaction, the catalyst being prepared by a method of preparation via a galvanic displacement reaction including a step of removing foreign metals from the surface or a galvanic displacement reaction including a pretreatment step.

[0011] Another aspect of the present invention provides a method for preparing a fuel cell catalyst.

[0012] Another aspect of the present invention provides a fuel cell comprising the fuel cell catalyst.

[0013] In a general sense, a fuel cell catalyst comprises a conductive support and core-shell nanoparticles supported on the support. The core contains platinum and transition metals, and the shell contains a dissimilar metal. The electrochemical specific activity, measured in an O2-saturated 0.1M HClO4 electrolyte solution at a scan rate of 5 mV / s and a rotation rate of 1,600 rpm over a potential range of 0.05 V to 1.05 V (vs. RHE), is 0.3 mA / cm². 2 Up to 0.6 mA / cm 2 And the mass activity is 0.05 mA / μg to 0.08 mA / μg.

[0014] The transition metal may be one or more selected from the group consisting of cobalt (Co), nickel (Ni), copper (Cu), and iron (Fe).

[0015] The dissimilar metal may be one or more selected from the group consisting of silver (Ag), gold (Au), palladium (Pd), and iridium (Ir).

[0016] The conductive carrier can be one or more selected from the group consisting of carbon black, Ketjen black, and metal oxides.

[0017] The diameter of the core-shell nanoparticles can be from 3 nm to 6 nm, and the thickness of the shell can be from 0.3 nm to 1.0 nm.

[0018] The specific electrochemical activity of the fuel cell catalyst, measured in an O2-saturated 0.1M HClO4 electrolyte solution at a scan rate of 5 mV / s and a rotation rate of 1,600 rpm within a potential range of 0.05 V to 1.05 V (vs. RHE), was 0.4 mA / cm². 2Up to 0.6 mA / cm 2 The mass activity ranges from 0.06 mA / μg to 0.08 mA / μg.

[0019] In another general aspect, a method for preparing a fuel cell catalyst includes: preparing a core-support particle dispersion (S1) by dispersing core-support particles, which have a core containing platinum and a transition metal loaded on a conductive support, in an organic solvent and stirring the dispersion under a reducing gas atmosphere; performing a galvanostatic displacement reaction by mixing the core-support particle dispersion with a heterometallic precursor solution to produce a mixture (S2); and washing and drying the mixture, followed by heat treatment under a reducing gas atmosphere (S3). The galvanostatic displacement reaction includes: preparing the core-support particle dispersion into an acidic dispersion with a pH of 2 to 5, and then stirring and mixing the dispersion with the heterometallic precursor solution (S2-1); or preparing a dispersion containing core-shell nanoparticles by stirring and mixing the core-support particle dispersion with the heterometallic precursor solution, then washing and drying the dispersion containing core-shell nanoparticles, followed by heat treatment to prepare primary core-shell nanoparticles, and then dispersing the primary core-shell nanoparticles in an acidic solution with a pH of 2 to 5 (S2-2).

[0020] The core-carrier particles can be prepared by mixing and reacting an organic solution containing a conductive carrier with an organic solution containing a platinum precursor and a transition metal precursor, followed by washing and drying the mixture.

[0021] The dispersion described in (S1) can be achieved through ultrasonic treatment.

[0022] The acidic dispersion in (S2-1) can be prepared by adding acid to the core-carrier particle dispersion under a reducing gas atmosphere.

[0023] The heterometal precursor solution in (S2) can be prepared by dissolving the heterometal precursor in an organic solvent. The heterometal precursor can be one or more compounds selected from the group consisting of nitrides, chlorides, sulfides, acetates, acetylacetonates, cyanides, and hydrates of the heterometal.

[0024] The stirring and mixing described in (S2-1) and (S2-2) can be carried out by stirring the solution for 12 to 24 hours.

[0025] The acidic solution in (S2-2) can be a solution of acetic acid dissolved in alcohol at 1M to 3M.

[0026] The heat treatment described in (S3) can be carried out in a reducing gas atmosphere at 300°C to 900°C.

[0027] In another general aspect, a fuel cell includes: a positive electrode; a negative electrode opposite to the positive electrode; and an electrolyte membrane located between the positive electrode and the negative electrode, wherein at least one of the positive electrode and the negative electrode contains the fuel cell catalyst.

[0028] Other features and aspects will become apparent from the following detailed description, drawings and claims. Attached Figure Description

[0029] The above and other aspects, features and advantages of the present invention will become more clearly understood from the following detailed description taken in conjunction with the accompanying drawings, in which:

[0030] Figure 1A-1D This is a TEM image of the fuel cell catalyst of Example 1. Figure 1A It is a HAADF-STEM image. Figure 1B It is a Pt EDX element diagram. Figure 1C It is an Ag EDX element diagram. Figure 1D This is an EDX elemental diagram of Pt-Co / Ag.

[0031] Figure 2A-2D This is a TEM image of the fuel cell catalyst of Comparative Example 1. Figure 2A It is a HAADF-STEM image. Figure 2B It is a Pt EDX element diagram. Figure 2C It is an Ag EDX element diagram. Figure 2D It is a Pt / Ag EDX element diagram.

[0032] Figures 3A-3D This is a TEM image of the fuel cell catalyst of Example 2. Figure 3A It is a HAADF-STEM image. Figure 3B It is a Pt EDX element diagram. Figure 3C It is an Au EDX element diagram. Figure 3D It is a Pt / Au EDX element diagram.

[0033] Figures 4A-4D This is a TEM image of the fuel cell catalyst of Comparative Example 2. Figure 4A It is a HAADF-STEM image. Figure 4B It is a Pt EDX element diagram. Figure 4C It is an Au EDX element diagram. Figure 4D It is a Pt / Au EDX element diagram.

[0034] Figure 5 These are current-voltage diagrams of the fuel cell catalysts of Example 1 and Comparative Example 1;

[0035] Figure 6These are the current-voltage diagrams of the fuel cell catalysts of Example 2 and Comparative Example 2;

[0036] Figure 7 This is a graph showing the mass activity of the fuel cell catalysts of Example 1, Example 2, Comparative Example 1, and Comparative Example 2. Detailed Implementation

[0037] Exemplary embodiments of the present invention will be described in detail with reference to the accompanying drawings.

[0038] It should be understood that the words or terms used in the specification and claims of this invention should not be construed as having meanings limited to those defined in common dictionaries. It should be further understood that, based on the principle that the inventors can appropriately define the meanings of words or terms to best interpret the invention, the words or terms should be interpreted as having meanings consistent with their meanings in the context of the relevant field and the technical concept of the invention.

[0039] [Terminology Definition]

[0040] As used in this article, the term "galvanic displacement reaction" refers to a spontaneous oxidation / reduction reaction in which metals and metal ions exchange electrons with each other. The process in which metals with different ionization tendencies, such as copper (Cu), are immersed in a solution containing silver (Ag) ions, causing the copper to be oxidized and dissolved, while the silver ions are reduced and precipitated on the copper surface to form a silver plating layer, is called galvanic displacement reaction.

[0041] As used in this article, the term "dissimilar metal" refers to a metal that has a different ionization tendency than transition metals and can undergo galvanic displacement reactions.

[0042] As used in this article, the term "room temperature" refers to the temperature under natural conditions without heating or cooling, which is 20 ± 5 °C.

[0043] It will be further understood that the terms “comprising,” “including,” and “having,” and their derivatives as used herein, whether or not specifically disclosed, are not intended to exclude the presence or addition of optional ingredients, steps, or processes. To avoid any uncertainty, unless otherwise stated, all materials and methods claimed using the term “comprising” may include optional additional additives, auxiliaries, or compounds, including catalysts or any other materials. Conversely, the term “consistently composed of” excludes optional ingredients, steps, or processes from the scope of the optional, continuous description that are not necessary for operation. The term “consisting of” excludes optional ingredients, steps, or processes that are not specifically stated or listed.

[0044] [Measurement Methods and Conditions]

[0045] In this specification, "electrochemical specific activity" and "electrochemical mass activity" are defined by preparing a catalyst ink by dispersing 0.005 g of catalyst in a mixed solution of Nafion solution (5 wt%) and isopropanol (IPA), and then dropping the catalyst ink onto a rotating disk electrode (19.6 mm). 2 The working electrode was prepared by drying the electrode, using an SCE electrode as the reference electrode and a platinum wire as the counter electrode. The prepared three-phase electrode was placed in a 0.1M HClO4 electrolyte solution, saturated with oxygen, and its activity was measured at a scan rate of 5mV / sec, a voltage range of 0.05-1.05V (vs. RHE), and a rotation rate of 1,600rpm.

[0046] fuel cell catalyst

[0047] This disclosure provides a fuel cell catalyst that exhibits excellent redox activity and improved mass activity due to the increased electrochemical reaction active area.

[0048] According to one embodiment of this disclosure, a fuel cell catalyst comprises a conductive support and core-shell nanoparticles supported on the support, wherein the core comprises platinum and a transition metal, and the shell comprises a dissimilar metal. The specific electrochemical activity, measured in an O2-saturated 0.1M HClO4 electrolyte solution at a scan rate of 5 mV / s and a rotation rate of 1,600 rpm within a potential range of 0.05 V to 1.05 V (vs. RHE), is 0.3 mA / cm². 2 Up to 0.6 mA / cm 2 .

[0049] Furthermore, the electrochemical mass activity of the fuel cell catalyst, measured in an O2-saturated 0.1M HClO4 electrolyte solution at a potential range of 0.05V to 1.05V (vs. RHE) at a scan rate of 5mV / s and a rotation rate of 1,600rpm, can be from 0.05mA / μg to 0.08mA / μg.

[0050] In particular, the specific electrochemical activity of the fuel cell catalyst, measured in an O2-saturated 0.1M HClO4 electrolyte solution at a scan rate of 5 mV / s and a rotation rate of 1,600 rpm within a potential range of 0.05 V to 1.05 V (vs. RHE), is 0.4 mA / cm². 2 Up to 0.6 mA / cm 2 The mass activity ranges from 0.06 mA / μg to 0.08 mA / μg.

[0051] According to embodiments of this disclosure, the fuel cell catalyst is prepared by a preparation method including a galvanocoupler displacement reaction, which includes a post-treatment step for removing foreign metal nanocrystals or a pre-treatment step for acid treatment, as described later. Thus, under the driving conditions of the fuel cell, the dissolution of transition metals on the catalyst surface is suppressed, which can reduce the foreign metal nanocrystals remaining on its surface, increase the active area of ​​the electrochemical reaction, improve the mass activity, and therefore has excellent redox reaction activity.

[0052] The conductive support can be used without particular restrictions, as long as it is a conductive support commonly referred to as a core-shell nanoparticle support. For example, it can be one or more selected from the group consisting of carbon support and metal oxide, specifically one or more selected from the group consisting of carbon black, Ketjen black and metal oxide (ITO, Nb-doped TiO2, Ti4O7, AZO).

[0053] Core-shell nanoparticles may comprise a core containing a platinum-transition metal and a shell containing a dissimilar metal formed around the core. The diameter of the core-shell nanoparticles may be 3 nm to 6 nm, and the thickness of the shell may be 0.3 nm to 1.0 nm. If the shell thickness is less than the above range, the transition metal present in the core may dissolve, leading to corrosion; if the shell thickness is greater than the above range, the performance of the catalyst may deteriorate.

[0054] Furthermore, there are no particular limitations on the transition metal, as long as it is known in the art, and it can be one or more selected from the group consisting of cobalt (Co), nickel (Ni), copper (Cu), and iron. Preferably, the transition metal can be one or more selected from the group consisting of cobalt and copper.

[0055] Furthermore, the dissimilar metal is not particularly limited, as long as it can readily undergo an electrocoupled substitution reaction with a transition metal. It can be one or more selected from the group consisting of gold (Au), silver (Ag), platinum (Pt), palladium (Pd), and iridium (Ir). Preferably, the dissimilar metal can be one or more selected from the group consisting of gold and silver.

[0056] Furthermore, based on a platinum atomic ratio of 100 parts by weight in the core, the atomic ratio of transition metals in the fuel cell catalyst can be 10-30 parts by weight, or 15-25 parts by weight, preferably 20 parts by weight. If the atomic ratio of transition metals is less than the above range, the content of transition metals that can improve the activity of platinum may be insufficient, leading to a decrease in electrochemical activity. If the atomic ratio of transition metals is greater than the above range, the adsorption capacity of platinum for oxygen species may be excessively reduced, leading to a decrease in electrochemical activity, or the transition metals may be exposed on the catalyst surface and dissolve from the surface, leading to a decrease in electrochemical activity.

[0057] Preparation method of fuel cell catalyst

[0058] In addition, this disclosure provides a method for preparing a fuel cell catalyst.

[0059] The method for preparing a fuel cell catalyst according to embodiments of the present disclosure includes the following steps: dispersing core-support particles containing a platinum and a transition metal core on a conductive support in an organic solvent, and stirring the dispersion under a reducing gas atmosphere to prepare a core-support particle dispersion (S1); performing a galvanic displacement reaction by mixing the core-support particle dispersion with a heterogeneous metal precursor solution (S2); and washing and drying the mixture, followed by heat treatment under a reducing gas atmosphere (S3), wherein the galvanic displacement reaction in step (S2)... The process is carried out through the following steps: preparing the core-carrier particle dispersion into an acidic dispersion with a pH of 2 to 5, and then mixing the dispersion with a heterogeneous metal precursor solution (S2-1); or preparing a dispersion containing core-shell nanoparticles by mixing the core-carrier particle dispersion with the heterogeneous metal precursor solution, then washing and drying the dispersion containing core-shell nanoparticles, followed by heat treatment to prepare primary core-shell nanoparticles, and then dispersing the primary core-shell nanoparticles in an acidic solution with a pH of 2 to 5 (S2-2).

[0060] Step (S1)

[0061] Step (S1) is the preparation of a core-carrier particle dispersion from which oxygen species have been removed from the surface. This can be done by dispersing core-carrier particles containing platinum and transition metal cores loaded on a conductive support in an organic solvent and stirring the dispersion in a reducing gas atmosphere.

[0062] There are no particular restrictions on the organic solvent, as long as it is known in the art, and it can be one or more selected from the group consisting of ethanol, anhydrous ethanol, methanol, isopropanol, acetone and dimethylformamide.

[0063] In addition, the dispersion in step (S1) can be carried out by ultrasonic treatment. Specifically, the core-carrier particles can be dispersed by adding the core-carrier particles to an organic solvent and ultrasonic treatment for 30 minutes to 1 hour, followed by stirring the dispersion for 30 minutes to 1 hour.

[0064] In addition, a reducing gas atmosphere is an environment that can remove oxygen species from a dispersion, which can be formed by injecting, for example, hydrogen, argon, or a mixture thereof.

[0065] Furthermore, the core-carrier particles can be prepared by mixing and reacting an organic solution containing a conductive carrier with an organic solution containing a platinum precursor and a transition metal precursor, followed by washing and drying the mixture.

[0066] Since the conductive carrier has already been explained above, its explanation will be omitted here.

[0067] There are no particular restrictions on the platinum precursor, as long as it is known in the art, but it can be one or more compounds selected from the group consisting of H2PtCl6, H2PtCl4, K2PtCl6, K2PtCl4 and PtCl2(NH3)4.

[0068] In addition, there are no particular limitations on the transition metal precursors, as long as they are known in the art. They can be one or more compounds selected from the group consisting of transition metal nitrides, chlorides, sulfides, acetates, acetylacetonates, cyanides and hydrates.

[0069] Organic solutions containing conductive supports and metal precursors can be prepared by adding and dissolving the conductive support and metal precursor separately in an organic solvent.

[0070] Step (S2)

[0071] Step (S2) is the formation of a shell containing a dissimilar metal on a core containing platinum and a transition metal. This can be carried out by mixing a dissimilar metal precursor solution with the core-carrier particle dispersion prepared in step (S1) and performing a galvanocoupler displacement reaction. In this case, the galvanocoupler displacement reaction can be carried out at room temperature.

[0072] The heterometal precursor solution can be prepared by adding and dissolving a heterometal precursor in an organic solvent. The heterometal precursor can be one or more compounds selected from the group consisting of nitrides, chlorides, sulfides, acetates, acetylacetonates, cyanides, and hydrates of the heterometal.

[0073] In this disclosure, the galvanic displacement reaction in step (S2) can be carried out through the following two different steps.

[0074] Step (S2-1)

[0075] Step (S2-1) can be carried out by preparing the core-carrier particle dispersion into an acidic dispersion with a pH of 2 to 5, and then mixing the dispersion with a heterogeneous metal precursor solution.

[0076] Acidic dispersions can be prepared by adding acid to a core-carrier particle dispersion under a reducing gas atmosphere. In this case, the acid can be used in an appropriate amount to make the pH of the acidic dispersion 2 to 5, especially 2 to 3.

[0077] Here, there are no particular restrictions on the acid; any substance commonly classified as an acid can be used as long as the pH can be formed immediately. For example, the acid can be an inorganic acid such as hydrochloric acid, nitric acid, sulfuric acid or perchloric acid, or an organic acid such as acetic acid, oxalic acid, tartaric acid or benzoic acid, with hydrochloric acid being preferred.

[0078] In this case, the formation of dissimilar metals as independent crystals on the catalyst surface can be suppressed by creating an acidic environment prior to the galvanocoupler displacement reaction.

[0079] Stirring can be carried out at room temperature for 12 to 24 hours.

[0080] Step (S2-2)

[0081] Step (S2-2) can be carried out by stirring and mixing the core-carrier particle dispersion with the heterogeneous metal precursor solution to prepare a dispersion containing core-shell nanoparticles, washing and drying the dispersion containing core-shell nanoparticles, then heat-treating it to prepare primary core-shell nanoparticles, and then dispersing the primary core-shell nanoparticles in an acidic solution with a pH of 2 to 5.

[0082] Here, the acidic solution can be a solution whose pH is adjusted by mixing distilled water or alcohol with an acid. The acid can be an inorganic acid such as hydrochloric acid, nitric acid, sulfuric acid or perchloric acid, or an organic acid such as acetic acid, oxalic acid, tartaric acid or benzoic acid, preferably acetic acid.

[0083] More specifically, the acidic solution may be a solution of acetic acid dissolved in an alcohol at a concentration of 1 M to 3 M.

[0084] Stirring can be carried out at room temperature for 12 to 24 hours.

[0085] In this case, the dissimilar metal crystals that form independently on the catalyst surface can be removed by acid treatment after the galvanic displacement reaction.

[0086] Step (S3)

[0087] Step (S3) is the process of washing, drying, and heat-treating the mixture to obtain the fuel cell catalyst.

[0088] Washing and drying can be carried out using methods known in the art. For example, washing can be done by adding alcohol and distilled water, and drying can be carried out at a temperature of 20°C to 100°C for 1 to 5 hours.

[0089] Alternatively, heat treatment can be carried out by methods known in the art, for example, at a temperature of 300°C to 900°C for 2 to 8 hours in a reducing gas atmosphere.

[0090] fuel cells

[0091] Furthermore, this disclosure provides a fuel cell comprising the fuel cell catalyst.

[0092] A fuel cell according to an embodiment of the present disclosure includes: a positive electrode; a negative electrode opposite to the positive electrode; and an electrolyte membrane located between the positive electrode and the negative electrode, wherein at least one of the positive electrode and the negative electrode contains the fuel cell catalyst.

[0093] The fuel cell disclosed herein comprises a catalyst layer with improved mass activity and excellent redox reactivity as the positive or negative electrode, thereby exhibiting excellent electrochemical reactivity.

[0094] Example

[0095] The invention will now be described in more detail with reference to embodiments. However, embodiments of the invention may be modified in many different ways, and the scope of the invention should not be construed as limited to the embodiments described below. Rather, embodiments of this disclosure are provided so that this disclosure will be sufficient and complete, and will fully convey the scope of this disclosure to those skilled in the art.

[0096] Example 1

[0097] Carbon-supported platinum-cobalt nanoparticle cores (0.1 g, TEC36E52, TKK, Ltd.) were added to 180 mL of anhydrous ethanol and sonicated for 30 min, followed by further stirring for 30 min. The mixture was then further stirred for 1 hour in a hydrogen / argon (5 / 95 wt%) atmosphere.

[0098] A silver precursor solution (0.007 g of silver precursor (silver acetate) dissolved in 20 mL of anhydrous ethanol) was added, and the mixture was stirred at room temperature for 12 hours. The mixture was then washed with ethanol and distilled water, dried in an oven at 70 °C for 3 hours, and heat-treated at 400 °C for 2 hours in a hydrogen / argon (5 / 95 wt%) atmosphere to prepare primary core-shell nanoparticles.

[0099] The prepared primary core-shell nanoparticles were dispersed in a 1M acetic acid / ethanol solution, stirred for 12 hours, washed with ethanol and distilled water, dried at room temperature, and then heat-treated again at 400°C for 2 hours in a hydrogen / argon (5 / 95 wt%) atmosphere to prepare a fuel cell catalyst.

[0100] Example 2

[0101] Carbon-supported platinum-cobalt nanoparticle cores (0.1 g, TEC36E52, TKK, Ltd.) were added to 180 mL of anhydrous ethanol and sonicated for 30 min, followed by further stirring for 30 min. A dispersion with pH 2 was then prepared by adding hydrochloric acid while stirring the mixture under an argon atmosphere.

[0102] The gold precursor solution (0.017 g of gold precursor (HAuCl4·xH2O) dissolved in 100 mL of anhydrous ethanol) was slowly added to the mixture at a rate of 24 mL / hr using a syringe pump, and the mixture was stirred at room temperature for 12 hours. The mixture was then washed with ethanol and distilled water, dried in an oven at 70 °C for 3 hours, and heat-treated at 400 °C for 2 hours in a hydrogen / argon (5 / 95 wt%) atmosphere to prepare the fuel cell catalyst.

[0103] Comparative Example 1

[0104] Carbon-supported platinum-cobalt nanoparticle cores (0.1 g, TEC36E52, TKK, Ltd.) were added to 180 mL of anhydrous ethanol and sonicated for 30 min, followed by further stirring for 30 min. The mixture was then further stirred for 1 hour in a hydrogen / argon (5 / 95 wt%) atmosphere.

[0105] A silver precursor solution (0.007 g of silver precursor (silver acetate) dissolved in 20 mL of anhydrous ethanol) was added, and the mixture was stirred at room temperature for 12 hours. The mixture was then washed with ethanol and distilled water, dried in an oven at 70 °C for 3 hours, and heat-treated at 400 °C for 2 hours in a hydrogen / argon (5 / 95 wt%) atmosphere to prepare the fuel cell catalyst.

[0106] Comparative Example 2

[0107] Carbon-supported platinum-cobalt nanoparticle cores (0.1 g, TEC36E52, TKK, Ltd.) were added to 180 mL of anhydrous ethanol and sonicated for 30 min, followed by further stirring for 30 min. The mixture was then further stirred for 1 hour in a hydrogen / argon (5 / 95 wt%) atmosphere.

[0108] A gold precursor solution (0.017 g of gold precursor (HAuCl4·xH2O) dissolved in 20 mL of anhydrous ethanol) was added, and the mixture was stirred at room temperature for 12 hours. The mixture was then washed with ethanol and distilled water, dried in an oven at 70 °C for 3 hours, and heat-treated at 400 °C for 2 hours in a hydrogen / argon (5 / 95 wt%) atmosphere to prepare the fuel cell catalyst.

[0109] Experimental Example 1

[0110] The fuel cell catalysts prepared in the examples and comparative examples were observed using transmission electron microscopy (TEM), and the results are shown in Figures 1 to 4.

[0111] Each fuel cell catalyst was dispersed in ethanol to prepare samples. In this case, all samples were prepared by dispersing equal amounts of catalyst in equal amounts of ethanol.

[0112] The prepared sample was dropped onto a TEM grid (Holey carbon-Cu 200 mesh, 50 micrometers), dried at room temperature to prepare the sample, and the TEM image was measured using a Talos F200X device at a magnification of 1.3 million times.

[0113] Referring to Figures 1 and 3, the fuel cell catalysts of Examples 1 and 2 confirm that silver or gold particles are uniformly coated on the surface of the platinum-cobalt core.

[0114] On the other hand, as shown in Figures 2 and 4, the fuel cell catalysts of Comparative Examples 1 and 2 confirmed that gold or silver independently formed crystals (agglomerates) on the platinum-cobalt core surface, and their distribution was not uniform.

[0115] Therefore, the method of this disclosure, which includes a step of removing foreign metal nanocrystals from the surface or a pretreatment step of acid treatment, and which includes a galvanostatic displacement reaction, can be confirmed as capable of preparing fuel cell catalysts that effectively undergo galvanostatic displacement reactions to uniformly form a shell and reduce the number of independent foreign metal nanocrystals remaining on the surface.

[0116] Experimental Example 2

[0117] The oxygen reduction reaction (ORR) characteristics of the fuel cell catalysts prepared in the examples and comparative examples were evaluated.

[0118] Each prepared catalyst (0.005 g) was dispersed in a mixed solution of Nafion solution (5 wt%) and isopropanol (IPA) to prepare catalyst ink. The catalyst ink was dropped onto a rotating disk electrode (19.6 mm). 2 The alcohol is then dried to evaporate it in order to prepare the working electrode.

[0119] The SCE electrode was used as the reference electrode, and the platinum wire was used as the counter electrode. All analyses were performed at room temperature.

[0120] The prepared three-phase electrode was placed in a 0.1M HClO4 electrolyte solution and saturated with oxygen, with oxygen continuously supplied during the analysis. The specific activity, mass activity, and half-wave potential of the catalyst were measured at a scan rate of 5 mV / sec, a voltage range of 0.05–1.05 V (vs. RHE), and a rotational speed of 1,600 rpm. The results are shown in Table 1 below. Figures 5 to 7 middle.

[0121] [Table 1]

[0122] Classification Mass activity (mA / μg) <![CDATA[Specific activity (mA / cm 2 )]]> Half-wave potential (mV) Example 1 0.069 0.56 929 Example 2 0.066 0.33 928 Comparative Example 1 0.038 0.29 903 Comparative Example 2 0.045 0.33 915

[0123] As shown in Table 1 and Figure 7 As confirmed, Examples 1 and 2 exhibited at least 0.05 mA / μg of mass activity and 0.3 mA / cm² of mass activity. 2 The specific activity was significantly increased compared to Comparative Examples 1 and 2.

[0124] Additionally, as shown in Table 1, Figure 5 and Figure 6 As shown, it is confirmed that compared with Comparative Examples 1 and 2, Examples 1 and 2 have higher starting potentials and half-wave potentials.

[0125] Meanwhile, the onset potential and half-wave potential are important standards for understanding the oxygen reduction reaction activity of a catalyst. The onset potential refers to the voltage at which the oxygen reduction reaction of a catalyst begins. If a catalyst exhibits a higher onset potential and a higher half-wave potential, it will have better electrochemical activity.

[0126] The fuel cell catalyst disclosed herein has the following effects: when the fuel cell is driven, the dissolution of transition metals in the catalyst surface is suppressed, the number of foreign metal nanocrystals remaining on its surface is reduced, thereby increasing the active area of ​​the electrochemical reaction and thus improving the mass activity, thereby exhibiting excellent oxygen reduction reaction activity.

[0127] Furthermore, the method for preparing the fuel cell catalyst disclosed herein can prepare a fuel cell catalyst with excellent activity through a galvanostatic displacement reaction including a pretreatment step of removing foreign metal nanocrystals on the surface or acid treatment.

[0128] Furthermore, the fuel cell disclosed herein includes a catalyst layer with improved mass activity and excellent redox reaction activity as the positive or negative electrode, thereby exhibiting excellent electrochemical reaction.

[0129] Although the invention has been shown and described in conjunction with exemplary embodiments, it will be apparent to those skilled in the art that modifications and variations may be made without departing from the spirit and scope of the invention as defined by the appended claims.

Claims

1. A fuel cell catalyst comprising: a conductive support; and a core-shell nanoparticle supported on the support, wherein the core comprising platinum and a transition metal, the shell comprising a heterometal, The electrochemical specific activity is 0.4 mA / cm 2 to 0.6 mA / cm 2 and the mass activity is 0.06 mA / µg to 0.08 mA / µg, wherein the electrochemical specific activity and the mass activity of the fuel cell catalyst are measured by preparing a catalyst ink by dispersing 0.005 g catalyst into a mixed solution of 5 wt% Nafion solution and isopropyl alcohol, dropping the catalyst ink onto a 19.6 mm 2 rotating disc electrode and drying to prepare a working electrode, placing the prepared three-phase electrode in a 0.1 M HCIO4 electrolyte solution, saturating the three-phase electrode with oxygen, and measuring activity at a scan rate of 5 mV / s, a voltage range of 0.05-1.05 V vs. RHE, and a rotation rate of 1,600 rpm, wherein the fuel cell catalyst is prepared by a method comprising: preparing a core-support particle dispersion (SI) by dispersing a core-support particle having a core comprising platinum and the transition metal supported on a conductive support in an organic solvent, and stirring the dispersion under a reducing gas atmosphere; producing a mixture by subjecting the core-support particle dispersion to an electroless displacement reaction with a heterometal precursor solution (S2); and washing and drying the mixture, and then heat-treating under a reducing gas atmosphere (S3), wherein the electroless displacement reaction is performed by: preparing a dispersion containing a core-shell nanoparticle by stirring mixing the core-support particle dispersion with the heterometal precursor solution, and then washing and drying the dispersion containing a core-shell nanoparticle, followed by heat-treatment to prepare a primary core-shell nanoparticle, and further dispersing the primary core-shell nanoparticle in an acidic solution having a pH of 2 to 5 (S2-2), wherein the transition metal is one or more selected from the group consisting of cobalt, nickel, copper, and iron, wherein the heterometal is one or more selected from the group consisting of silver, gold, palladium, and iridium.

2. The fuel cell catalyst of claim 1, wherein, the conductive support is one or more selected from the group consisting of carbon black, ketjen black, and a metal oxide.

3. The fuel cell catalyst of claim 1, wherein, the core-shell nanoparticle has a diameter of 3 nm to 6 nm and a shell thickness of 0.3 nm to 1.0 nm.

4. A method for producing the fuel cell catalyst according to claim 1, the method comprising: preparing a core-support particle dispersion (SI) by dispersing a core-support particle having a core comprising platinum and a transition metal supported on a conductive support in an organic solvent, and stirring the dispersion under a reducing gas atmosphere; producing a mixture by subjecting the core-support particle dispersion to an electroless displacement reaction with a heterometal precursor solution (S2); and washing and drying the mixture, and then heat-treating under a reducing gas atmosphere (S3), wherein the electroless displacement reaction is performed by: preparing a dispersion containing a core-shell nanoparticle by stirring mixing the core-support particle dispersion with the heterometal precursor solution, and then washing and drying the dispersion containing a core-shell nanoparticle, followed by heat-treatment to prepare a primary core-shell nanoparticle, and further dispersing the primary core-shell nanoparticle in an acidic solution having a pH of 2 to 5 (S2-2). the core-support particle is prepared by mixing and reacting an organic solution in which a conductive support is dissolved with a metal precursor organic solution in which a platinum precursor and a transition metal precursor are dissolved, and then washing and drying the mixture.

5. The method of claim 4, wherein, the dispersion in (SI) is performed by ultrasonic treatment.

6. The method of claim 4, wherein, the heterometal precursor solution in (S2) is prepared by dissolving a heterometal precursor in an organic solvent, and 7. The method of claim 4, wherein, ​ The heterogeneous metal precursor is one or more compounds selected from the group consisting of nitrides, chlorides, sulfides, acetates, acetylacetonates, cyanides, and hydrates of the heterogeneous metal.

8. The method of claim 4, wherein, The stirring mixing in (S2-2) is performed by stirring the solution for 12 hours to 24 hours.

9. The method of claim 4, wherein, The acidic solution in (S2-2) is acetic acid dissolved in an alcohol at 1M to 3M.

10. The method of claim 4, wherein, The heat treatment in (S3) is performed at 300°C to 900°C in a reducing gas atmosphere.

11. A fuel cell comprising: a positive electrode; a negative electrode opposite to the positive electrode; and an electrolyte membrane positioned between the positive electrode and the negative electrode, wherein, at least one of the positive electrode and the negative electrode comprising the fuel cell catalyst of claim 1.

Citation Information

Patent Citations

  • Temperature sensor, temperature measuring device, and temperature measuring method

    KR1020210114866A

  • Method for producing core-shell catalyst

    US20170214060A1